Fiscal policy, economic integration and unemployment - Wolfgang Eggert; Laszlo Goerke (Institute for the Study of Labor (IZA), 2003)
In this paper fiscal policy is examined for an open economy characterised by unemployment due to efficiency wages. We allow for capital and firm mobility in a model where the government chooses the level of wage, source-based capital and profit taxation. The taxing choices of governments are analyzed in scenarios which differ with respect to the constraints imposed on the set of available taxes and on the mobility of firms. As a general result, the welfare loss from labour market imperfections increases when tax bases become internationally mobile, which suggests an increasing relevance of domestic labour-market reforms when tax bases become global.
Keywords: J41; J65; H21; 330; optimal taxation; efficiency wages; unemployment; Finanzpolitik; Optimale Besteuerung; Kapitalertragsteuer; Arbeitslosigkeit; Effizienzlohn; Steuerwettbewerb; Kleines-offenes-Land; Wirtschaftsintegration; Theorie